Out-patient triple chronotherapy for the rapid treatment and maintenance of response in depression: feasibility and pilot randomised controlled trial. Issue 6 (24th November 2021) - Veale, David; Serfaty, Marc; Humpston, Clara; Papageorgiou, Andriani; Markham, Sarah; Hodsoll, John; Young, Allan H.
Abstract : Background: Triple chronotherapy (sleep deprivation for 36 h, followed by 4 days of advancing the time of sleep and daily morning bright-light therapy for 6 months) has demonstrated benefits for the rapid treatment of depressive symptoms in four small controlled trials of in-patients. Aims: To test the feasibility of recruitment and delivery of triple chronotherapy for out-patients with depression (ISRCTN17706836; NCT03405493). Method: In a single-blind trial, 82 participants were randomised to triple chronotherapy or a control intervention. The primary outcome was the number of participants recruited per month and adherence to the protocol. Secondary outcomes included the 6-item Hamilton Rating Scale for Depression (HRSD-6) at 1 week. Timings of observer ratings were baseline and 1, 2, 4, 8 and 26 weeks after randomisation. Results: The triple chronotherapy group stayed awake for the planned 36 h and 89.9% adhered to the plan of phase advance of their sleep over the following 4 days. We achieved our recruitment target (60 participants completed the trial within 13 months). There were no reported adverse side-effects. We found a significant difference between the groups by intention-to-treat analysis for the HRSD-6 at weeks 1, 8 and 26. There was a large effect size of Cohen's d = 0.8 on HRSD-6 score at week 1, increasing to d = 1.30 at week 26. A response (≥50% reduction in symptoms) was achieved by 33.3% in the triple chronotherapy group and 16.2% in the control group. This stayed relatively steady until week 26 (35.9 v . 13.9%). Conclusions: Triple chronotherapy produced a significant and rapid benefit after 1 week in out-patients with depression that was sustained at 26 weeks. Cost-effectiveness trials with a larger clinical sample are required.